INVENTARISASI AIR SUMUR SEBAGAI SUMBER AIR BERSIH DI DESA SUNGAI NIBUNG, KABUPATEN KUBU RAYA - Sofiana, Mega Sari Juane; Warsidah, Warsidah; Kushadiwijayanto, Arie Antasari; Apriansyah, Apriansyah; Safitri, Ikha; Rudiyanto, Rudiyanto; Nurrahman, Yusuf Arief; Minsas, Sukal; Idiawati, Nora; Helena, Shifa; Nurdiansyah, Sy. Irwan; Prayitno, Dwi Imam; Harianto, Harianto; Darma, Surya (Jurnal Indonesia Mengabdi, 2025)
A common problem faced by coastal communities is the lack of clean water kamislot. This issue also occurs in the coastal area of Sungai Nibung Village, Teluk Pakedai District, Kubu Raya Regency. The community relies on dug well water; however, this water is yellowish, murky, and has an iron odor. This activity, in Community Service (PKM), aims to collect data on the condition of water and existing clean water fasilities and infrastructure, and offer treatment solutions that consider the current situation. The method was carried out through field surveys, raw water sampling, simple water testing (pH, salinity, and coagulation-flocculation tests), and observation of clean water supporting facilities. High levels of in the water can be reduced through coagulation-flocculation using soda ash and PAC to precipitate the iron. If the sedimentation stage is skipped, the workload of the filters in te available facilities becomes heavier. One applicable solution for the community is to add aeration and sedimentation tanks to oxidize and precipitate the iron.